1981
DOI: 10.1029/wr017i002p00351
|View full text |Cite
|
Sign up to set email alerts
|

mass transport: 2. Analysis of uncertainty in prediction

Abstract: The first paper in this series presented a description of a stochastic modeling concept for mass transport. In this paper we extend that analysis to consider a more realistic set of. transport conditions in a groundwater basin with geologic layering, hydraulic anisotropy, spatial variations in porosity, and geochemical retardation. Uncertainties in transport predictions can be characterized by frequency distributions formed on the time of arrival of mass at the water table, on the exit location, and on the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(26 citation statements)
references
References 13 publications
(20 reference statements)
0
26
0
Order By: Relevance
“…1, but for small initial solute source sizes compared to the correlation scale, travel times need to be extremely large to reach the asymptotic limit. (3) Results differ greatly between individual porous medium realizations having the same stochastic parameters (Smith and Schwartz [37]). Therefore, to make predictions of solute concentrations in field situations (single realizations), not only ensemble averaged results are needed but also a measure of the deviation (uncertainty).…”
Section: Stochastic Transportmentioning
confidence: 97%
“…1, but for small initial solute source sizes compared to the correlation scale, travel times need to be extremely large to reach the asymptotic limit. (3) Results differ greatly between individual porous medium realizations having the same stochastic parameters (Smith and Schwartz [37]). Therefore, to make predictions of solute concentrations in field situations (single realizations), not only ensemble averaged results are needed but also a measure of the deviation (uncertainty).…”
Section: Stochastic Transportmentioning
confidence: 97%
“…When both the specific discharge through a unit area in the vertical section and the concentration of tritium in pore water are separated into the spatial mean and the spatial fluctuation, the convective flux of tritium averaged over the vertical section includes a term which is the average of product of fluctuations in both the specific discharge and the concentration. This term, which represents just the above mentioned dispersion caused by the inhomogeneity of flow field, corresponds to the so-called macro-dispersion (e. g., Freeze, 1975;Bear, 1979;Smith and Schwartz, 1981).…”
Section: Theorymentioning
confidence: 99%
“…Actually, the problem on the tritium distribution in groundwater flow systems has been left unsolved theoretically. Recently the problem on solute transport in inhomogeneous media has been investigated with stochastic modeling by several hydrologists (e. g., Freeze, 1975;Gelhar, et al, 1975;Smith and Schwartz, 1981;Dagan, 1982). In the present paper, a theoretical approach to the problem on the spatial distribution and time variation of tritium concentrations in an unconfined aquifer with a uniform input of tritium from precipitation will be made by investigating how far the influence of the dispersion due to inhomogeneity of media on the tritium distribution extends.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of three articles. Smith and Schwarz (1980, 1981a, 1981b determined that the major cause of dispersion in solute transport in porous media on a macroscopic scale was heterogeneity in hydraulic conductivity, not primarily a mechanical mixing process as represented in the advective-dispersive equation.…”
Section: Transport In Groundwatermentioning
confidence: 99%
“…Anderson concluded that dispersion was not a mixing process in field studies where large distances are traversed by the pollutant. Smith and Schwarz (1981a) Smith and Schwarz (1981b) concluded their analyses by investigating the effect of the amount of field data available on uncertainty in prediction. They concluded that field data significantly decrease uncertainty in transport prediction only in a small area around the location of the data and that considerable data collection is required to significantly decrease prediction uncertainty.…”
Section: Transport In Groundwatermentioning
confidence: 99%